2022
DOI: 10.22289/2446-922x.v8n2a14
|View full text |Cite
|
Sign up to set email alerts
|

HIPNOSE: definição, importância, limitações e possibilidades baseadas em evidências

Abstract: The primary objective of this review is to analyze the main theoretical perspectives that define hypnosis, the value of considering it as a unique phenomenon, the evidence that sustains that view, and its effect on research. For more than a century in which the subject has been studied, the results are still hampered by a methodological flaw since the beginning of the research, the definition of the phenomenon. This review used the Medline via Pubmed as database for bibliographic search, including a total of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
0
0
1
Order By: Relevance
“…Pode-se afirmar que o parto normal/vaginal/natural é amplamente recomendado e, nas situações que fogem da normalidade e oferecem riscos à saúde materna ou fetal, as intervenções são benéficas para o processo do nascimento. Conforme cientistas (19)(20) as principais indicações para realização da anteriores (21)(22) .…”
Section: Resultsunclassified
“…Pode-se afirmar que o parto normal/vaginal/natural é amplamente recomendado e, nas situações que fogem da normalidade e oferecem riscos à saúde materna ou fetal, as intervenções são benéficas para o processo do nascimento. Conforme cientistas (19)(20) as principais indicações para realização da anteriores (21)(22) .…”
Section: Resultsunclassified
“…Despite hypnosis being the first form of psychotherapy in the West (DeSouza et al, 2020) and the significant accumulation of evidence regarding functional brain changes associated with hypnosis (Wolf et al, 2022), Souza and Broering (2022) identified that the majority of hypnosis research is conducted from a state hypothesis theoretical line, varying between qualitative and quantitative views, weak state, and that many authors make minor alterations to their definitions of the hypnotic phenomenon, creating a spectrum of definitions without empirical foundation. Although most hypnosis research treats it as an altered state of consciousness, this definition of the phenomenon, in over 100 years of research, has not demonstrated a causal relationship between functional brain changes and the human capacity for response to suggestions (Mazzoni et al, 2013) and the identified changes in neural activity patterns.…”
Section: Introductionmentioning
confidence: 99%